HUBUNGAN JOB INSECURITY TERHADAP WORK ENGAGEMENT DENGAN INTERNAL LOCUS OF CONTROL SEBAGAI MODERATOR PADA GURU HONORER - Khoiroh, Atik (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2021)
Work engagement is an important aspect that must be owned by employees to improve their performance. Employees who have an attachment to their work have many advantages, they be able to maintain and increase productivity. Honorary teachers have the same responsibilities as permanent teachers in educating their students, but honorary teachers have not received appropriate compensation and dismissals without severance pay may occur to them. Therefore, they experience job insecurity. Teachers who have a high internal locus of control believe that the center of control in their lives is determined by themselves. This study aims to determine the relationship between job insecurity and work engagement with the internal locus of control as a moderator for honorary teachers. This research was conducted on 61 honorary teachers. Data analysis was carried out by moderated regressionanalysis. From the results of the analysis of the research data, it was obtained that the significance of the internal locus of control as a moderator of the relationship between job insecurity and work engagement was 0.724 > 0.05. Thus, there is no significant relationship between job insecurity and work engagement moderated by internal locus of control. So that Ho is accepted, there is no significant relationship between job insecurity and work engagement moderated by internal locus of control on honorary teachers.